Transit Oriented Development: a Solution for Station Areas Planning - Papa, Enrica (TeMA - Journal of Land Use, Mobility and Environment, 2008)
The need of reducing urban sprawl, the increasing number of motorized trips, the presence brownfields in strategic areas of cities, great investments in rail transport infrastructures, are all key elements that contribute to the diffusion of “Transit Oriented Development” theories and practices. In many cases applications of TOD principles are still complex, even though is widely recognized in theory the necessity of densify station areas with high quality and functional mix developments. Starting from this critical point, the main research question of this work is: how is it possible to “export” TOD principles and practices in Europe? The article try to answer this question through a comparative analysis of different best practice in Europe and through the definition of TOD procedures. The study analyses the TDA (Transport Development Area) approach proposed by the RICS in UK and the Stedebaan project in The Netherlands. Furthermore the research focuses on the France and Germany study cases, where the regional rail-oriented development is mainly connected with the HST lines construction and the rail network “regionalization” process. Also in Italy the important investment in rail infrastructures was the occasion for station area renewal and station area revitalising, but in most cases with an “urban design” approach rather than transport-land use integrated approach. The main conclusion stress the necessity of a new integrated approach and the definition of a “Station Plan” for the integration of urban and transport interventions.